The development of the chondrocranium of Spheniscus demersus, with special reference to the columella auris of birds - Crompton, A. W.(Alfred Walter) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1951.